Anterior segment imaging-based subdivision of subjects with primary angle-closure glaucoma - Nongpiur, M E; Atalay, E; Gong, T; Loh, M; Lee, H K; He, M; Perera, S A; Aung, T (Eye (London), 2017)
Purpose The purpose of this study was to identify whether it was possible to subdivide subjects with primary angle-closure glaucoma (PACG) based on anterior segment optical coherence tomography (ASOCT) imaging, and to determine the characteristics of such subgroups. Methods We evaluated 210 subjects with PACG. All subjects underwent gonioscopy and ASOCT imaging. Customized software was used to measure ASOCT parameters. An agglomerative hierarchical clustering method was first used to determine the optimum number of parameters to be included in the determination of subgroups. Then, the best number of subgroups was determined using Akaike Information Criterion (AIC) and Gaussian Mixture Model (GMM) methods. Results The mean age of the subjects was 67.9 years, and 53.3% were female. Following the hierarchical clustering, four parameters (iris area, anterior chamber depth (ACD), anterior chamber width (ACW), and lens vault (LV)) were chosen to be representative of related parameters. The optimal number of subgroups using GMM analysis and AIC was 3. Subgroup 1 ( N =89; 42.4%) was characterized by a large iris area, subgroup 2 ( N =24; 11.4%) by a large LV and a shallow ACD, whereas subgroup 3 ( N =97; 46.2%) displayed only intermediate values across iris area, LV, and ACD. Conclusions We identified three distinct subgroups of PACG subjects based on ASOCT imaging.